2011
DOI: 10.1021/nl202214y
|View full text |Cite
|
Sign up to set email alerts
|

A Reel-Wound Carbon Nanotube Polarizer for Terahertz Frequencies

Abstract: Utilizing highly oriented multiwalled carbon nanotube aerogel sheets, we fabricated micrometer-thick freestanding carbon nanotube (CNT) polarizers. Simple winding of nanotube sheets on a U-shaped polyethylene reel enabled rapid and reliable polarizer fabrication, bypassing lithography or chemical etching processes. With the remarkable extinction ratio reaching ∼37 dB in the broad spectral range from 0.1 to 2.0 THz, combined with the extraordinary gravimetric mechanical strength of CNTs, and the dispersionless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…[8][9][10] In addition, polarizers based on highly aligned single-walled carbon nanotube (SWNT) films (either on substrates or free-standing) have been demonstrated to have promising performance in the THz region. 11,12 However, the available approaches either require complex (i.e., costly) or chemically aggressive fabrication steps, or are hindered by limitations in carbon nanotube film formation, growth, and transfer. Due to the above, existing approaches limit the choice of substrates and are frequently detrimental to the environment by generating hazardous waste.…”
Section: Quasi-optical Terahertz Polarizers Enabled By Inkjet Printinmentioning
confidence: 99%
“…[8][9][10] In addition, polarizers based on highly aligned single-walled carbon nanotube (SWNT) films (either on substrates or free-standing) have been demonstrated to have promising performance in the THz region. 11,12 However, the available approaches either require complex (i.e., costly) or chemically aggressive fabrication steps, or are hindered by limitations in carbon nanotube film formation, growth, and transfer. Due to the above, existing approaches limit the choice of substrates and are frequently detrimental to the environment by generating hazardous waste.…”
Section: Quasi-optical Terahertz Polarizers Enabled By Inkjet Printinmentioning
confidence: 99%
“…Lei Ren et al reported a highly aligned SWCNT film of a thickness of 2 micrometers, deposited on a sapphire substrate, transparent to terahertz (THz) radiation polarized perpendicular to the nanotube axis with an extinction ratio of about 10dB [4]. Later, Kyoung et al, by winding MWCNT sheets on a U-shaped polyethylene frame, obtained free-standing CNT layers of 9 micrometer thickness with an extinction ratio ~37dB in a spectral region from 0.1-2THz [5].…”
Section: Abstract-we Have Performed Optical Investigations Of Layersmentioning
confidence: 99%
“…Lei Ren et al reported a highly aligned SWCNT film of a thickness of 2 micrometers, deposited on a sapphire substrate, transparent to terahertz (THz) radiation polarized perpendicular to the nanotube axis with an extinction ratio of about 10dB [4]. Later, Kyoung et al, by winding MWCNT sheets on a U-shaped polyethylene frame, obtained free-standing CNT layers of 9 micrometer thickness with an extinction ratio ~37dB in a spectral region from 0.1-2THz [5].Herein we explore the optical properties of highly aligned MWNT sheets on glass substrate in the visible wavelength range finding a clear anisotropy in the optical transmission as an effect of the CNT alignment.Since, CNT sheets are attractive transparent electrodes due to their electrical conductivity and optical transparency, the study of their anisotropic properties and the dependence on the structural organization is of great importance for developing optical devices such as liquid crystal displays. In particular, the quality of the alignment of CNT strands is expected to be relevant for the properties of the sheets since it determines the anisotropy in the characteristics and, as consequence, the performance of the layers in optical devices or as a templating system.…”
mentioning
confidence: 99%
“…More recently, using extremely well aligned ultralong carbon nanotubes, Ren and co-workers demonstrated that carbon nanotubes can be perfect THz polarizers [60]. Kyoung and co-workers used aligned multi-wall carbon nanotubes to demonstrate similarly strong anisotropy [61].…”
Section: Thz Antennae and Polarizersmentioning
confidence: 99%